2021
DOI: 10.1108/jwl-11-2020-0179
|View full text |Cite
|
Sign up to set email alerts
|

I want to learn more! Integrating technology acceptance and task–technology fit models for predicting behavioural and future learning intentions

Abstract: Purpose Constant and frequent technological changes within organizations call for further scholarly attention, as behavioural intentions need to be coupled also with future learning intentions to predict the present and prospective individual adaptations and performance. This study, grounded on the technology acceptance model, aims to examine the association between training opportunities and behavioural and future learning intentions also taking into account the role of task–technology fit as a moderator. D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
8
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 39 publications
3
8
0
Order By: Relevance
“…On the one hand, Norzaidi and Salwani’s (2009) empirical evidence does not support TTF’s predictive power towards Internet usage. On the other hand, Presti et al. ’s (2021) findings confirm the indirect association between TTF and behavioral and future mobile learning intentions.…”
Section: Literature Review and Conceptual Frameworksupporting
confidence: 68%
“…On the one hand, Norzaidi and Salwani’s (2009) empirical evidence does not support TTF’s predictive power towards Internet usage. On the other hand, Presti et al. ’s (2021) findings confirm the indirect association between TTF and behavioral and future mobile learning intentions.…”
Section: Literature Review and Conceptual Frameworksupporting
confidence: 68%
“…It is helpful because, if workers have low perceptions of support, employers can work on communication plans focused on technological innovations, their benefits, and emphasize the willingness to support employees when introducing new tools. Finally, few studies investigated the TAM in an Italian working context (see [90]). To the best of our knowledge, no studies have investigated the intention to use apps for the promotion of well-being in such contexts.…”
Section: Discussionmentioning
confidence: 99%
“…Chang (2013) investigated the acceptance and utilization characteristics of library application acceptability and found that TTF played a major moderating influence. A study was done (Lo Presti et al, 2021) to evaluate the relationship between training opportunities and future learning goals. The study was based on the technology acceptance model, although TTF was used as a moderator variable.…”
Section: Task Technology Fit (Ttf)mentioning
confidence: 99%